Robust Recursive Inverse Adaptive Algorithm in Impulsive Noise - Ahmad, Mohammad Shukri; Kukrer, Osman; Hocanin, Aykut (Springer Birkhauser, 2012)
The recently proposed Recursive Inverse (RI) algorithm has shown a significant performance improvement compared to that of the Recursive Least Squares (RLS) algorithm, in various noise environments. However, both algorithms fail to converge in certain impulsive noise environments, especially if the Signal-to-Noise Ratio (SNR) is low. In this paper, a Robust RI algorithm is proposed. Analytical results show that robustness against impulsive noise is achieved by choosing the weights on the basis of the L (1) norms of the autocorrelation matrix and the cross-correlation vector. Simulation results confirm that the proposed algorithm provides an improved performance, with a reduction in computational complexity, compared to those of the RLS and the Robust RLS in white and correlated impulsive noise.
Keywords: Adaptive filters; Robust RLS; RI algorithm; Impulsive noise